2006
DOI: 10.2105/ajph.2004.051193
|View full text |Cite
|
Sign up to set email alerts
|

Urban–Rural Inequalities in Ischemic Heart Disease in Scotland, 1981–1999

Abstract: Low standardized ratios of IHD continuous hospital stays and mortality in remote rural areas mask health problems among rural populations. Although absolute and relative differences between urban and rural rates of MH+ have diminished, the relative risk of MH+ remains high in remote rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
2
30
1
1
Order By: Relevance
“…Indeed studies have shown that limiting long term illnesses (LLTI) are more prevalent in more remote rural areas in the South West (Barnett, Roderick, Martin, & Diamond, 2001) and the East of England (Haynes & Gale, 2000) than in rural areas located on the urban fringe. Similar within-rural variations regions were also observed for overall mortality (Bentham, 1984) and for the risk of ischemic heart disease mortality in the hospital or within 28 days of discharge (Levin & Leyland, 2006a). Other studies have reported variation in LLTI (Levin, 2003) and mental health (Weich et al, 2006) across rural areas but this variation was generally smaller than that observed across urban areas.…”
Section: Introductionsupporting
confidence: 63%
“…Indeed studies have shown that limiting long term illnesses (LLTI) are more prevalent in more remote rural areas in the South West (Barnett, Roderick, Martin, & Diamond, 2001) and the East of England (Haynes & Gale, 2000) than in rural areas located on the urban fringe. Similar within-rural variations regions were also observed for overall mortality (Bentham, 1984) and for the risk of ischemic heart disease mortality in the hospital or within 28 days of discharge (Levin & Leyland, 2006a). Other studies have reported variation in LLTI (Levin, 2003) and mental health (Weich et al, 2006) across rural areas but this variation was generally smaller than that observed across urban areas.…”
Section: Introductionsupporting
confidence: 63%
“…Therefore, we performed analyses that examined the association between time to transplantation and distance from the closest transplant center after stratifying on these potential confounders. The time to transplantation was not significantly lower among remote dwellers for any of these subgroups than for those (14) 4862 (14) 3812 (14) 511 (15) 572 (16) (1) 1580 (1) 1908 (2) 1021 (3) 1746 (6) 508 (14) 440 (13) Other 20 096 (6) 8161 (5) 1746 (2) 549 (2) 649 (2) 49 (1) (14) 5097 (15) 3845 (14) 529 (15) 501 (14) Ͻ.001 CVD 24 275 (7) 12 676 (7) 8754 (8) 3020 (9) 2139 (8) 290 (8) (6) 1938 (7) 240 (7) 643 (19) Abbreviations: BMI, body mass index, calculated as weight in kilograms divided by height in meters squared; CAD, coronary artery disease; CHF, congestive heart failure; COPD, chronic obstructive pulmonary disease; CVD, cerebrovascular disease; eGFR, estimated glomerular filtration rate; ESRD, end-stage renal disease; PVD, peripheral vascular disease; RUCA, rural-urban commuting area. Conversion factor: To convert miles to kilometers, multiply by 1.6. a Totals do not always add to 100% because of rounding.…”
Section: Likelihood Of Transplantation By Distance Categorymentioning
confidence: 99%
“…The results presented were for a unit change in deprivation as measured by the SIMD score divided by ten, with the assumption that each additional unit carries an equivalent effect. Rurality was included as a categorical variable as defined by the 2008 Scottish Household Survey urban-rural classification (35) and used in similar analyses elsewhere (13)(14)(15)36) . Of the original 3577 young people surveyed, 894 (25 %) were excluded due to missing postcode information, 54 % boys and 46 % girls.…”
Section: Explanatory Variablesmentioning
confidence: 99%